Electrochemical sensor for detecting ascorbic acid molecules and preparation method thereof

The LEG electrode is prepared through the CO2 laser carving and the marking polymer of its surface electrical sedimentary molecular marks to form a PPD/LEG electrode, which solves the lack of accuracy and reliability of existing AA detection methods, and achieves high sensitivity and specific AA detection.

CN119355072APending Publication Date: 2025-01-24SHANGHAI TONGJI HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411360079.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing ascorbic acid (AA) detection methods are insufficient in accuracy and reliability, especially in complex biological environments, which are difficult to achieve high sensitivity and specific detection.

Method used

The LEG electrode is prepared by CO2 laser carving technology, and a PPD/LEG electrode is formed through the molecular seal polymer (MIPS) polymer (MIPS) technology on its surface to improve the specific identification and detection capabilities of AA.

Benefits of technology

It achieves the detection of AA in the ultra-low concentration range of 10-100nM, with a detection limit of 6.13nM, which significantly improves the sensitivity and specificity of the detection, and has good stability and repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355072A_ABST
    Figure CN119355072A_ABST
Patent Text Reader

Abstract

The invention relates to an electrochemical sensor for detecting ascorbic acid molecules and a preparation method of the electrochemical sensor. Specifically, the electrochemical sensor is obtained by electrically depositing a molecularly imprinted polymer on the surface of an LEG electrode. According to the invention, graphene is integrated and synthesized on the surface of the electrochemical sensor electrode by using a laser engraving technology, so that the performance of the electrode is effectively improved; meanwhile, the polymer is electrically deposited on the surface of the LEG electrode by using an MIP method, so that the specific recognition and ultrahigh-sensitivity detection of AA are improved, and the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of small molecule detection, and particularly relates to an electrochemical sensor for detecting ascorbic acid molecules and a preparation method thereof. Background Art

[0002] Various small molecules are important biomarkers for various diseases and have practical value in clinical diagnosis and treatment. Among them, ascorbic acid (AA), also known as vitamin C, has abnormal concentration levels in the human body, which can lead to scurvy, cardiovascular disease, increased risk of Parkinson's disease, low immunity, and may even cause cancer. Therefore, accurate and quantitative detection of AA is crucial for early diagnosis and treatment. However, due to the large number of other small molecules in the complex biological environment of the human body, such as dopamine (DA), uric acid (UA) and L-tyrosine (L-Tyr), and the inherent susceptibility to oxidation of AA molecules, it is difficult to accurately and sensitively detect AA in clinical evaluation. Traditional AA detection methods include chromatography, spectrophotometry, etc. However, these methods often have disadvantages such as high cost, the need for skilled operators, and complex analytical procedures for multi-sample preparation.

[0003] In recent years, electrochemical detection technology has developed rapidly. Due to the advantages of faster measurement time, better cost-effectiveness and elimination of pre-concentration process, various electrochemical sensors have been used to detect AA, including electrodes modified with metals and metal oxides, graphene derivatives, carbon nanotubes and polymers. For example, a study designed to fix platinum (Pt) single atoms doped with inorganic cesium lead bromide (CsPbBr3) nanocrystals on glassy carbon electrodes as electrochemical catalysts, and used its excellent electrochemical catalytic properties to provide an electrochemical strategy for AA detection. The results showed that the detectable AA concentration range was 1μM-50μM, and the detection limit (LOD) was 0.0369M; another study prepared vertical N by carbonizing Schiff base foam vertically grown on three-dimensional kenaf stalk porous carbon (3D-KSC). -doped carbon nanosheets / three-dimensional porous carbon nanocomposite materials (3D-KSC / C-CSBP). The electrochemical sensor based on the nanocomposite material can detect AA in the linear range of 1.98mM-6mM, with a detection limit of 0.66mM; similarly, there is an electrochemical sensor constructed with three-dimensional nitrogen-doped laminated porous carbon (NHPC) as the material, through carbonized cellulose nanocrystals (CNCs) and urea, which can detect AA in the linear range of 1μM-50μM, with a detection limit of 0.24μM.

[0004] In view of the existing research results, it is necessary to find a better electrode material that allows a faster electron transfer rate and has the ability to specifically capture target analytes, so as to further expand the linear range of AA detection, improve the sensitivity and specificity of detection, and at the same time have a certain stability and repeatability. Summary of the invention

[0005] The present invention provides an electrochemical sensor for detecting ascorbic acid molecules and a preparation method thereof, which solves the technical problem that the existing detection methods and technologies are still somewhat lacking in detection accuracy and reliability.

[0006] The invention provides an electrochemical sensor for detecting ascorbic acid molecules, which is obtained by electro-depositing molecular imprinting polymer on the surface of LEG electrode.

[0007] Preferably, the polymer is poly-o-phenylenediamine.

[0008] The present invention also provides a method for preparing an electrochemical sensor for detecting ascorbic acid molecules, comprising the following steps:

[0009] (1) Silver conductor, counter electrode and reference electrode are printed layer by layer on a polyimide film, and then the working electrode is laser engraved using a CO2 laser engraving machine to obtain a LEG electrode;

[0010] (2) preparing a prepolymerization solution of monomers and ascorbic acid, covering the prepolymerization solution on the LEG electrode for electrodeposition and polymerization, washing and drying, and obtaining the electrochemical sensor.

[0011] Preferably, the counter electrode in step (1) is carbon, and the reference electrode is Ag / AgCl.

[0012] Preferably, the process parameters of the laser engraving in step (1) are: laser power 3-8 W, defocus distance 3-5 mm, scanning rate 10-20 cm / s, and pulses per inch 1000-1500.

[0013] Preferably, the monomer in step (2) is o-phenylenediamine, and the molar ratio of the monomer to ascorbic acid is 1:2.

[0014] Preferably, the solvent used in the prepolymerization solution in step (2) is an acetate buffer solution.

[0015] Preferably, the process parameters of the electrodeposition in step (2) are: voltage 0.1v-0.8v.

[0016] The electrochemical sensor of the present invention combines multiple technologies, including CO2 laser engraved graphene (LEG) technology, which is a highly conductive and cost-effective electrochemical process that is expected to be used for high-sensitivity detection of AA. Using a CO2 laser, sp3 hybridized carbon can be converted into sp2-hybridized carbon through photothermal or photochemical effects. The graphene structure produced by this conversion has a high specific surface area, excellent thermal stability, excellent electronic conductivity and catalytic activity. The LEG electrode has a porous three-dimensional network structure, a large specific surface area and excellent conductivity, and is considered to be an ideal sensing element for detecting sensitive molecules. Compared with traditional graphene materials, LEG has high precision and high resolution, and is easy to process at the micro and nano levels. At the same time, Raman spectroscopy analysis shows that the prepared LEGs have fewer defects and layers.

[0017] The present invention also includes the application of molecular imprinting polymer (MIPs) technology, which is one of the main methods for developing highly selective materials by simulating the natural antigen-antibody reaction mechanism. This technology stands out by synthesizing the target template in the polymer, and has the advantages of low cost, high selectivity, simple operation, etc. It is an ideal modification material for the electrochemical sensor platform. By electropolymerizing molecular imprinting poly(p-phenylenediamine) (PPD) film on the surface of the LEG electrode, the PPD / LEG electrode is prepared, which provides a customized recognition site for AA and enhances the specificity of the sensor to the target molecule. Therefore, the integrated sensing strategy based on the MIP and LEG method is expected to achieve high sensitivity and specificity detection of AA in complex environments. The research results show that the sensor can detect AA in an ultra-low concentration range of 10-100nM, and the detection limit is 6.13nM. It is 1-2 orders of magnitude higher than the LOD detection method of the traditional electrochemical detection method, and compared with other related electrochemical sensing devices, it also has high sensitivity and a wider detection concentration range. This method has broad application prospects in the detection of low-concentration small molecule biomarkers in early clinical disease diagnosis.

[0018] Beneficial Effects

[0019] The present invention realizes the integration of synthetic graphene on the surface of electrochemical sensor electrode by laser engraving technology, effectively improving the performance of the electrode; at the same time, the polymer is electrodeposited on the surface of LEG electrode by MIP method, which improves the specific recognition and ultra-high sensitivity detection of AA, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the principle of the electrochemical sensor of the present invention.

[0021] Figure 2(a) is the LEG electrode; (b) is the SEM characterization of the LEG electrode; (c) is the Raman spectrum of the LEG electrode under optimized CO2 laser parameters; (d) is the planar SEM characterization of the PPD / LEG electrode; (e) is the SEM characterization cross-section of the prepared PPD / LEG electrode; (f) is the FT-IR curve of the LEG electrode and the PPD / LEG electrode.

[0022] Figure 3 (a) and (b) are cyclic voltammetry (CV) characterizations of LEG electrode and PPD / LEG electrode in 1 mm AA solution and PBS buffer solution; (c) is the cyclic voltammetry (CV) characterizations of LEG electrode and PPD / LEG electrode in 0.1 M [Fe(CN)6] 3- / 4- EIS analysis in redox probe; (d) differential pulse voltammetry (DPV) response curve of PPD / LEG electrode in 1 mm AA solution.

[0023] Figure 4 (a) and (b) are the calibration curves obtained using the PPD / LEG electrode in the micromolar concentration range; (c) and (d) are the chronoamperometric detection of AA by the PPD / LEG electrode and the calibration curves obtained in the nanomolar concentration range.

[0024] Figure 5 (a) Evaluation of the selectivity of the PPD / LEG electrode; (b) Evaluation of the repeatability of the PPD / LEG electrode; (c) Evaluation of the stability of the PPD / LEG electrode. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0026] Example 1

[0027] 1. Materials: AA, DA, UA, glacial acetic acid (analytical grade), ferric chloride (FeCl3), potassium dicyanide (K3[Fe(CN)6]), and potassium chloride (KCl) were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., China. Anhydrous sodium acetate and o-phenylenediamine (analytical grade, 98%) were purchased from Aladdin.

[0028] 2. Device: The surface morphology of the PPD / LEG electrode was analyzed using a scanning electron microscope (SEM, JEM 2100F, Nippon electron Corporation). The Fourier transform infrared (FT-IR) spectrum of the PPD / LEG electrode was analyzed using a Nicolet iS50 FT-IR spectrometer (Thermo Fisher, USA). The electrochemical detection method used a CHI660 electrochemical workstation equipped with a three-electrode system (Chen Hua, Shanghai, China). Laser engraving was performed using a laser engraver (TrotecSpeedy 100R, Austria).

[0029] 3. Such as Figure 1 As shown, prepare the LEG electrode:

[0030] First, the PI film used as an electrode was cleaned with anhydrous alcohol and then dried naturally. Silver (Ag) conductive paste was used as the silver conductor, carbon (C) conductive paste was used as the counter electrode, and silver / silver chloride (Ag / AgCl) conductive paste was used as the reference electrode. The silver conductor, counter electrode, and reference electrode were printed layer by layer on the polyimide film (PI film) in the order of layer 1 and dried at room temperature. Then, the working electrode was laser engraved using a CO2 laser engraver at a laser power of 5W, a defocus distance of 5mm, a scanning rate of 10cm / s, and a pulse number per inch (PPI) of 1000. The size of the laser-engraved working electrode was 3.5mm.

[0031] 4. Preparation of integrated PPD / LEG electrodes based on MIP:

[0032] The acetic acid buffer solution of o-phenylenediamine (o-PD) and AA at pH = 5.6 with a molar ratio of 1:2 was used as the prepolymerization solution. The LEG electrode was scanned for 10 cycles at 0.8v to -0.8v cyclic voltammetry (CV) and then dried for use. Then, the prepolymerization solution (100μL) was covered on the LEG electrode, and after 20 cycles of electrodeposition at 0.8v, the excess AA on the electrode surface was cleaned with deionized water and dried to obtain a PPD / LEG electrode.

[0033] 5. Sample Measurement Methods Cyclic voltammetry (CV), differential pulse voltammetry (DPV), electrochemical impedance spectroscopy (EIS), and chronoamperometry were performed using a CHI660 electrochemical workstation equipped with a three-electrode system.

[0034] 6. Test results:

[0035] (1) Figure 2As shown in Figure b, the prepared LEG electrode was characterized by scanning electron microscopy (SEM). The graphene on the LEG electrode has a uniform and dense porous foam structure, which is attributed to the release of gas molecules during the laser engraving process and can be used as an initial indicator of the successful formation of graphene structure on the polyimide (PI) film. At the same time, the Raman spectrum of LEG is shown in Figure 2. Figure 2 As shown in Figure c, it shows obvious D, G and 2D peaks, which are the characteristics of multilayer graphene. The intensity ratios ID / IG and I2D / IG are 0.692 and 0.794, respectively, indicating that the prepared graphene has fewer defects and layers, which provides a solid foundation for the excellent electron transport ability of the LEG electrode. Figure 2 As shown in (d), SEM characterization after electrodeposition of polymerized PPD on the LEG surface shows smaller imprinted cavities attached to the LEG pores. The emergence of this multi-level pore structure is due to the elution of template molecules during the MIP process. Figure 2 e illustrates the multilayer structure of PPD / LEG from a lateral perspective. In such a multilevel pore structure, the lower LEG has a fast electron transfer ability, which improves the sensitivity of AA detection, while the upper PPD has a higher electron transfer ability. The formation of the PPD / LEG electrode was further verified by Fourier transform infrared spectroscopy (FT-IR spectrometer), as shown in Figure 2 f, from 3385cm -1 and 3360cm -1 The appearance of two absorption peaks clearly shows the polymerization of the PPD film on the LEG electrode surface, confirming the polymerization of the PPD film on the LEG surface.

[0036] (2) Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), differential pulse voltammetry (DPV) and chronoamperometry analysis showed that the electrochemical reaction area of ​​the electrode was wider and the multi-level pore structure increased the electron transfer rate. Figure 3 In a, the bare LEG electrode shows a peak of AA at a relatively low potential (0.04 V vs. Ag / AgCl), which may be due to the oxidation of AA on the electrode surface to dehydroascorbic acid. It is worth noting that the peak potential of the LEG electrode is lower than that recorded previously by the electrochemical method for AA detection, indicating the enhanced electron transfer and excellent response to AA in the prepared LEG electrode. Figure 3 b shows the response of the PPD / LEG electrode prepared based on the MIP method to AA. Obviously, the expansion of the area surrounded by the CV curve indicates that the capacitance of the PPD / LEG electrode has increased, indicating that the electrochemical reaction area of ​​this electrode is wider. Figure 3 c shows the LEG and PPD / LEG electrodes in 0.1 M [Fe(CN)6] 3- / 4-]EIS detection in the redox probe shows that the charge transfer resistance (Rct) of the PPD / LEG electrode is reduced compared with the LEG electrode, indicating that the multi-level pore structure of the PPD / LEG electrode improves the electron transfer rate. In addition, Figure 3 d shows that the PPD / LEG electrode can significantly detect AA at 0.02 V relative to Ag / AgCl. This finding is consistent with the results obtained by CV, further supporting the feasibility and effectiveness of the PPD / LEG electrode in detecting AA.

[0037] (3) In order to verify the high sensitivity of the constructed PPD / LEG electrode to AA, the electrode was subjected to chronoamperometric measurements at different concentrations (0.1 V vs. Ag / AgCl, for 100 s). Figure 4 In a, the current value gradually increases with the increase of concentration. This trend is attributed to the continuous binding of AA into specific cavities in the PPD membrane and the oxidation reaction on the electrode surface. Figure 4 b It can be seen that the AA concentration is linearly related to the current change value. Similarly, Figure 4 c shows the time-temperature curve of the PPD / LEG electrode for detecting the nanomolar concentration of AA. Compared with the blank (PBS solution), the current change at 10nM is about 3.32nA, and the signal rises steadily with the increase of AA concentration. The change of AA concentration at low concentration is still linear with the change of current value. Using the 3-fold signal-to-noise ratio (S / N) criterion, the detection limit (LOD) of this method is determined to be 6.13nM. In PBS buffer solution, the electrode can distinguish the current signals of AA concentrations of 10, 20, 50, 80 and 100nM, with high sensitivity of AA detection.

[0038] (4) Finally, the specificity of the electrode in mixed solutions containing different concentrations of AA, DA, and UA was tested, and the repeatability and stability of the electrode were evaluated. Figure 5 As shown in a, the peak position of AA remains at 0.02 V vs. Ag / AgCl, and the current value increases with the increase in AA concentration, indicating that DA and UA do not interfere with the response to AA, which may be due to the specific binding affinity of the MIP cavity on the electrode surface for AA molecules. At the same time, the peak positions of DA and UA are stable at 0.25 V and 0.5 V, respectively, relative to Ag / AgCl. However, the responsiveness of the PPD / LEG electrode to changes in DA and UA concentrations is limited. This limitation is due to the fact that the MIP cavity on the electrode surface cannot effectively bind to DA and UA molecules, which confirms the selectivity of the PPD / LEG electrode for AA. In order to evaluate the reproducibility, PPD / LEG electrodes were randomly selected for DPV detection of 1 mM AA. As shown Figure 5As shown in (b), the current signal remains very stable, indicating that the prepared integrated electrode has good reproducibility. For stability testing, the LEG electrode was monitored for 7 days to observe the fluctuation of the 1 mM AA DPV current signal after PPD electropolymerization. Figure 5 c shows that after 7 days, the PPD / LEG electrode is almost indistinguishable from the original DPV response with an RSD of 6.94%, indicating that the sensor has good stability. It further demonstrates that the integrated sensing system has excellent electrochemical performance, the ability to accurately detect AA in mixed solutions, excellent reproducibility and stability, and the potential for highly sensitive and specific detection of AA.

Claims

1. An electrochemical sensor for detecting ascorbic acid molecules, characterized in that: It is obtained by electrodeposition of molecularly imprinted polymers on the surface of LEG electrodes.

2. The electrochemical sensor according to claim 1, characterized in that: The polymer is poly-o-phenylenediamine.

3. A method for preparing an electrochemical sensor for detecting ascorbic acid molecules, comprising the following steps: (1) Silver conductor, counter electrode and reference electrode are printed layer by layer on a polyimide film, and then the working electrode is laser engraved using a CO2 laser engraving machine to obtain a LEG electrode; (2) preparing a prepolymerization solution of monomers and ascorbic acid, covering the prepolymerization solution on the LEG electrode for electrodeposition and polymerization, washing and drying, and obtaining the electrochemical sensor.

4. The preparation method according to claim 3, characterized in that: The counter electrode in step (1) is carbon, and the reference electrode is Ag / AgCl.

5. The preparation method according to claim 3, characterized in that: The process parameters of the laser engraving in step (1) are: laser power 3-8W, defocus distance 3-5mm, scanning rate 10-20cm / s, and pulse number per inch 1000-1500.

6. The preparation method according to claim 3, characterized in that: The monomer in step (2) is o-phenylenediamine, and the molar ratio of the monomer to ascorbic acid is 1:

2.

7. The preparation method according to claim 3, characterized in that: The solvent used in the prepolymerization solution in step (2) is an acetate buffer solution.

8. The preparation method according to claim 3, characterized in that: The process parameters of the electrodeposition in step (2) are: voltage 0.1v-0.8v.